Effect of computerization on the transparency of service delivery in the selected government ministries in Anambra State Nigeria between the periods of 2015 - 2023 - Anaekwe, Victor Benjamine; Okoye, Nonso Sunday; Okeke, Mary Ngozi (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
The rapid advancement of information technology has transformed public sector operations globally. In Nigeria, government ministries increasingly adopt computerization to improve transparency and efficiency. The study adopted a survey research design using structured questionnaires to collect data from 294 staff across four ministries (Education 112, Finance 114, Works 38, Women Affairs 30) in Anambra State. The population of 1,105 staff was sampled using Yaro Yamane’s formula with a 5% margin of error. Data included both primary (questionnaires) and secondary (documents, literature) sources. The questionnaire, validated through expert review and pretested with 30 health ministry staff, utilized a four-point Likert scale. SPSS software handled data analysis, applying descriptive statistics and independent samples t-test to test hypotheses. Reliability was confirmed using Cronbach’s alpha. The findings reveal that financial resources (47.6% strongly agree), leadership support (38.4% strongly agree), and IT infrastructure (53.1% agree) strongly influenced e-administration transparency. Training received mixed responses, with 32.3% strongly agreeing, while interdepartmental collaboration had 40.5% agreeing. Opinions varied on project management (39.8% strongly disagree, 34.7% strongly agree) and stakeholder engagement (40.5% strongly disagree). Data security raised concerns (56.8% strongly disagree), while change management (56.5% agree) and continuous monitoring (45.9% strongly agree) received positive responses. Statistical analysis showed employees with first degrees (mean 30.83) outperformed postgraduates (mean 28.29), with significant differences (p = 0.001), suggesting educational background influenced e-administration service delivery. The study confirmed that computerization improved transparency and service delivery in Anambra State ministries, driven by financial support, leadership commitment, IT infrastructure, training, and monitoring. Challenges included data security and stakeholder engagement. Educational background influenced adaptability, with first-degree holders performing better. Strengthening weak areas can enhance digital governance outcomes. The study recommends strengthening data protection measures and adopting inclusive stakeholder management practices to maximize the benefits of e-administration